Seizure Characteristics and Background Amplitude-Integrated Electroencephalography Activity in Neonatal Rats Subjected to Hypoxia–Ischemia - Sun, Xiaowei; Xue, Fenqin; Wen, Jialin; Gao, Limin; Li, Yang; Jiang, Qianqian; Yang, Lijun; Cui, Hong (Frontiers in Pediatrics, 2022)
Objective: Perinatal hypoxic-ischemic encephalopathy (HIE) is a major cause of epilepsy and chronic neurologic morbidity in premature infants. This study aimed to investigate the characteristics of acute seizures and the pattern of background activity on amplitude-integrated electroencephalography (aEEG) in neonatal rats with HIE. Methods: Hypoxia-ischemia (HI) was induced in postnatal day (P) 3 neonatal rats (n=12) by ligation of the left carotid artery and exposure rats to airtight hypoxia for 2 h. Data regarding seizure type, frequency, and duration and those related to neurobehavioral development were collected, and the Integrated power of background EEG was analyzed to evaluate the effect of HI. Results: All the neonatal rats in the HI group experienced frequent seizures during hypoxia, 83.3% (10/12) experienced seizures immediately following hypoxia. Seizure frequency and duration gradually decreased with increasing age. The mortality rate of the HI group was 8.33% (1/12). At 120 h after HI induction, only 27.3% (3/11) of pups had low-frequency and short-duration electrographic seizures, respectively. HI rats, which presented seizure activities after 96h after HI insult, exhibited an increase in righting reflex time and a decrease in forelimb grip reflex time. The background EEG was significant inhibited during HI induction and immediately after hypoxia, and gradually recovered 72 hours after hypoxia. Conclusions: Seizures caused by HI brain damage in premature infants can be simulated in P3 neonatal rat model.